Split Personality Choreographer Rafael Bonachela in conversation - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Choreographer Rafael Bonachela in conversation. He has always been able to make us watch, now he's also trying to make us feel. PALABRAS CLAVE: Rafael Bonachela, Bonachela Dance Company (BDC), music and video's messages.